Characterization of plasmonic metamaterials using surface enhanced raman spectroscopy - Goh, Geat Yee (2015)
Metamaterial consists of artificially engineered metallic nanostructures, which can give rise to novel emerging material properties. In this work, the feasibility of various metamaterial structures as sensing platform is theoretically and experimentally explored. Resonator geometries studied in this work are the split-ring resonator and rotationally symmetric structures such as star-like and swastika-like metallic nanostructure, where their spectral performances in the presence of refractive index changes are compared and discussed. The sensing capability is studied characterizing the red-shift in the transmission spectra of the metallic nanostructure in question under different claddings materials, where distilled water, isopropanol, and acetone are used for liquid cladding, and 100-nm thick polymethylmethacrylate (PMMA) is used for the solid cladding. For completeness, each metallic nanostructures are also theoretically studied, where finite difference time domain (FDTD) simulations are used for obtaining scattering properties and is on-resonance electromagnetic fields distributions.